FRI0500 Daily practice of ultrasonography in 53 departments of rheumatology during 3 years follow up : the french experience. (23rd January 2014) - Gandjbakhch, F.; Etchepare, F.; Jousse-Joulin, S.; Marcelli, C.; Bertola, J. P.; Bourgeois, P.
Abstract : Background: The use of Ultrasonography (US) in rheumatology has considerably increased in the last few years. Evaluation of national osteoarticular US practice may lead to adapt trainings to increase standardization of US practice. Objectives: To describe daily practice of US in French departments of rheumatology in a national multicentre longitudinal study of 3 years follow up. Methods: Each year (T1, T2, T3), questionnaires were sent in order to collect informations concerning the experience of the centres in US practice and ultrasonographers' experience and practice use. Daily US practice was evaluated by collecting data (indication and results of US examinations) for all US examination performed during one month (September to October) each year. This evaluation was repeated during 3 years. Results: During the 3 years follow up, the number of centres, of ultrasonographers and of US examinations performed per month increased considerably (table ). Sonographers were young (mean: 37± 7, 9 years) and have been practicing US for (mean) 4 years. 96% of them at T3 had a diploma for US practice (85% at T0) and 89% of them still participated to formations on US after their diploma. 64% used systematic examination for each pathology and 56 % used scoring systems. The 2398 US examinations per month at T3 were performed for inflammatory rheumatisms (60%), mechanical diseases (30%), other indications like Horton/PMR or Gougerot-Sjogren(10%). Concerning inflammatory rheumatism, US were mostly performed for rheumatoid arthritis (RA) (42%) (equally for diagnosis and follow up), for spondyloarthropathy (28%) (essentially for diagnosis) and for unclassified rheumatism (20%). RA examination was quite consensual among rheumatologists as more than 80% of the rheumatologists examined wrists, MCP 2 to 5, PIP 2 to 5 and MTP 2 to 5 for diagnosis and wrists, MCP 2 to 5 and MTP5 for follow up. Concerning Spondyloarthritis, there was no consensus for the joints to examine, but the examination of enthesis was homogeneous with more than 80 % of the rheumatologists practicing examination of the enthesis of lateral epicondyle tendon, patellar ligament, quadricipital tendon, calcaneum tendon and plantar aponevrosis. Conclusions: This national multicentre longitudinal study demonstrated the widespread of US practice among the departments of rheumatology in France in a 3 years follow up. US examinations concerned mostly inflammatory diseases and appeared homogeneous among rheumatologists for RA and for SpA enthesis examinations. Yet, this study showed that only 56% of the rheumatologists used scoring systems and further training and formations should be necessary in order to improve standardization. Disclosure of Interest: None Declared